The Crisis of the Single Market. EU Legislation for the Response to Emergencies and Crisis on the European Market - Muskaj, Blerina (European Journal of Multidisciplinary Studies, 2023)
A well-functioning and resilient single market remains a fundamental resource for the European Union economy to create and distribute wealth to its citizens. The facts demonstrate that in recent years the crisis and the problems of many countries have interrupted the normal functioning of the common market, with inevitable consequences on the social and economic cohesion of the European Union. The supply challenges that have occurred over the years in several critical sectors, including, in particular, the healthcare sector, have drawn the attention of the European institutions to the importance of strengthening the sustainability of the common market and industrial ecosystems by addressing, in particular , the weaknesses of the sectors in a strategic way and mitigating disruptions (even preventively) in a more efficient and coordinated way.  During the pandemic crisis, unilateral measures adopted by Member States and the lack of transparency have damaged the fundamental freedoms of the common market, with significant and already evident economic and social consequences. This situation represented the "challenge" that has so far put the European Union system in the greatest difficulty in recent history, which in order to deal with this crisis due to the spread of covid 19, member states have intervened autonomously, adopting non-homogeneous measures that have been imposed and implemented at the national level, including border closures. After this phase of uncertainty, states began to find common solutions and promote common policies with soft law instruments, and as such, on the one hand, fast, flexible and easy to use but with more important legitimacy deficits, which have been approved by deviating from the legislative procedure foreseen by the treaties and by the absence of a judge.
Keywords: European Union, SMEI, European Commission, IPCR, ERCC, European Convention